Edukasi dan Pemberian Informasi Obat Penyakit Diabetes Melitus di Kampung Biru: Community Education and Drug Information Provision on Diabetes Melitus in Kampung Biru - Mulyani, Risya; Hafizah, Nurul; Riauwati, Rossa; Sukmawati, Anita; Hairi, Dewi Gulyla; Mulyani, Evi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The high prevalence of disease and limited public understanding of appropriate medication use prompted the implementation of a community service program in Kampung Biru, Banjarmasin City. This activity aimed to enhance community knowledge of degenerative diseases through group-based education, post-tests, satisfaction surveys, and the distribution of educational materials and drug information by the service team. The program involved collaboration among 17 pharmacy education institutions, healthcare professionals from the local health center (Puskesmas), and professional organizations. A total of 58 participants attended the event, 10 of whom were identified with elevated blood glucose levels. Evaluation results indicated an increase in average post-test scores compared to pre-test scores, reflecting improved understanding following the educational intervention. Challenges such as time constraints and limited participant numbers were addressed by dividing the group and rotating service schedules. Educational leaflets were also provided to reinforce comprehension. Most participants reported high satisfaction and demonstrated better awareness regarding their health conditions and the proper, safe use of medications. This program contributed positively to increasing public awareness of the importance of preventing and managing degenerative diseases, particularly diabetes mellitus.